A POLÍTICA DE DESLOCAMENTOS NOS POEMAS CIVIS DE JOAN BROSSA - Bittencourt, Rita Lenira de Freitas (Organon, 2012)
the book Poemas Civis, translated by Ronald Polito and Sergio Alcides, is a Catalan/Portuguese bilingual production, published in 1998. It is Joan Brossa’s first edition in Portuguese and, according to the translators, the original publication, from 1961, was partial, since it suffered cuts due to censorship. Additionally, it was only by the end of the dictatorship in Spain in 1977 that its edition was completed. For that reason, this selection of poems, part of a literary work, is considered that which more explicitly exposes political issues. Apart from obvious contextual references, the verses promote the indissociability between the poetry and the visual art, between the word and the object, the organic and the prosthetic, a project which would be developed by the poet, with notable coherence, throughout his life. The reading this article proposes considers the miscellany of languages and Brossa’s interest in exhibiting the creative materiality, indications of a diction which strategically escapes norms and explores the effects of a politics of displacements, which being acute is also astute.